The Mathematical Model of Integrated Coupling of Gas Reservoir-Wellbore-Choke in Sulige Gas Field, China. (7th June 2022) - Han, Zizi; An, Yongsheng; Guo, Ping; Jiang, Chengyin; Feng, Yinghai; Zhang, Qiang
Abstract : The tight sandstone gas has huge objective reserves in China and great potential for development. The Sulige gas field is the largest tight sandstone gas field in China. To prevent hydrates and reduce surface pipeline pressure, downhole throttling technology has been widely used in the Sulige gas field, China. Since gas wells in the Sulige gas field are prone to liquid accumulation during production, the installation of downhole chokes makes the liquid accumulation phenomenon of gas wells more complicated, and traditional methods are difficult to simulate and predict production performance. In order to solve this problem, based on the establishment of the gas reservoir seepage model, the wellbore pipe flow model, and the choke nozzle flow model, the gas reservoir-wellbore-choke integrated coupling mathematical model and its solution method were proposed. The case calculation of the choke well in the Sulige gas field is presented. The research results show that the new integrated coupled mathematical model can fully reflect the impact of choke installation and fishing on fluid accumulation and is effectively used for the production performance simulation of choke wells in the Sulige gas field.